Razian Authority and Law - Specyal, James M. (My University, 2012)
In this thesis, I will examine the consequences of applying the legal philosophy of Joseph Raz in real world situations. I will argue that if most legal systems actually attempted to adhere to, and accept his theory in all its parts, the legal systems in question would have serious problems. In particular, the legal authorities and officials which represent the legal systems in question would be confused about the extent of their authority. After I prove my claim, I will offer a solution to the problem.
Keywords: Raz; legal philosophy; service conception; Other Philosophy; Other Philosophy